Profiles of cardiometabolic risk and acculturation indicators among South Asians in the US: latent class analysis of the MASALA study - Montiel Ishino, Francisco A.; Canenguez, Katia M.; Cohen, Jeffrey H.; Kent, Blake Victor; Villalobos, Kevin; Needham, Belinda L.; Kandula, Namratha R.; Kanaya, Alka M.; Shields, Alexandra E.; Williams, Faustine (Frontiers in Public Health, 2024)
South Asians (SA) represent the fastest growing US immigrant group, and previous studies have indicated that they face disproportionately high burden of cardiometabolic disease. Cardiometabolic disease manifests as a syndemic or synergistic epidemic encompassing multiple disease clusters influenced by biological, social, and psychological factors stemming from the acculturative process. This process may exacerbate morbidity within immigrant subgroups. Our aim was to identify cardiometabolic risk profiles among SA using indicators of acculturation. To achieve this, we conducted latent class analysis on data from the Mediators of Atherosclerosis in South Asians Living in America study (N=771). A composite cardiometabolic disease outcome was constructed using prevalent hypertension, type 2 diabetes, and body mass index. Acculturation indicators included years living in the US, English language proficiency, dietary behaviors, preservation of cultural traditions, social and neighborhood support, maintenance of social relationships (i.e., friendships), and experiences of discrimination, along with proxies of acculturative stress (i.e., depressive symptomology, trait anxiety and anger). Social and environmental determinants of health, health behaviors, religiosity and spirituality served as covariates to further assess latent class membership. Four cardiometabolic risk profiles emerged: (1) lowest risk [73.8% of sample] characterized by high integration into both SA and US cultures; (2) the modest risk [13.4% of sample], exhibiting elevated levels of mental health distress and experiences of discrimination, and distancing themselves from both cultures; and the (3) moderate risk [8.9% of sample] and (4) highest risk [3.9% of sample], demonstrating greater assimilation into US culture. Compared to the lowest risk profile: the modest risk profile was associated with low-income and conflicting attitudes about religion/spirituality, while the moderate risk profile was characterized by lower income and educational attainment with positive behaviors and attitudes toward religion/spirituality. Findings expand our understanding of immigrant cardiometabolic health as a syndemic issue wherein multiple co-occurring and interacting processes synergize to produce negative outcomes in already at-risk subpopulations. Furthermore, acculturation emerges as a crucial factor in understanding health disparities among immigrant and refugee groups in the US.